KELIMPAHAN DAN KEANEKARAGAMAN SPESIES SERANGGA PREDATOR DAN PARASITOID Aphis gossypii DI SUMATERA SELATAN - . Riyanto; Siti Herlinda; Chandra Irsan; Abu Umayah (Universitas Lampung, 2011)
This study was aimed to analysis abundance and species diversity of predatory insects and parasitoid of Aphis gossypii from lowland and highland areas of South Sumatra. Survey of was conducted in 11 vegetable centers of South Sumatra. The results showed that 20 species of predatory insects and 3 species of parasitoids were found from the survey. The predatory insects consisted of 15 species of coccinellid beetles, two species of syrphids, and one species of chamaemyiid, mantid and staphylinid. Parasitoid found were 2 species of Aphidiidae (Diaretiella rapae and Aphidius sp.) and a species of Aphelinidae (Aphelinus sp.). The highest abundance of the predator was found in Soak (42.61 larvae and adults) and the highest abundance of the parasitoid was found in Talang Buruk (25.99 adults). The highest species diversity of the predator and the parasitoid were found in Soak (15 species and H’= 0.94) and in Talang Buruk (2 species and H’ = 0.27), respectively. Abundance and species diversity of the predators and parasitoids were higher in the dry season than those in rainy season. Thus, the abundance and species diversity of the predators and parasiotids were higher in the lowland than highland areas in South Sumatra, while the seasons affected the abundance and species diversity of the predators and parasitoids.